Adding value to INSAT-3D sea surface temperature fields using MODIS data over the tropical Indian Ocean. Issue 5 (4th May 2017) - Jangid, Buddhi Prakash; Prakash, Satya; Bushair, M. T.; Kumar, Raj
ABSTRACT: Accurate estimates of sea surface temperature (SST) are crucial for climate studies, numerical weather prediction and air–sea interactions. Following the launch of India's advanced geostationary satellite – INSAT-3D with two thermal infrared split window channels in 2013, it is now possible to monitor land and ocean surfaces more reliably at higher spatiotemporal scale. In this article, an attempt has been made to develop a more accurate infrared-based cloud-free SST estimates over the tropical Indian Ocean by the synergistic use of geostationary INSAT-3D and polar-orbiting Aqua Moderate Resolution Imaging Spectroradiometer (MODIS) satellite measurements through a successive correction method. This method is applied primarily for the month of May 2015 at coarser spatial resolution and at a daily scale. Results are compared independently with multi-satellite SST estimates and also against in situ observations such as Argo floats and buoys. The merged SST product shows noticeable improvement over INSAT-3D-based estimates alone. Comparison of the merged SST product with Argo observations shows that the root mean square difference (RMSD) has been improved from 1.23 to 0.79 K, and bias and correlation are also significantly improved. Overall results indicate that the synergistic use of INSAT-3D and MODIS satellite observations has potential for more accurate SST estimation over the tropical Indian Ocean at finer temporal resolution and larger spatial coverage for several near-real time meteorological and oceanographic applications.